Social Family Support for Children with Special Needs in Special School Care for Nagari Children Akabiluru District - Saputri Kelana (International Journal Labs, 2021)
This research was conducted on the basis of the discovery of phenomena that exist in the Nagari Children's Care Special School, Akabiluru District which shows that family social support for children with special needs is still lacking such as emotional support. The purpose of this research is to find out Family Social Support for Children with Needs at the Nagari Children's Care Special School, Akabiluru District. This research is descriptive qualitative. Informants in this study consist of key informants parents of children with special needs and supporting informants, namely one mentally retarded child and one autistic child. Data were collected by conducting observation and interview guidelines. The data processing technique used descriptive qualitative analysis and the technique of testing the validity of the data was by data triangulation. Based on the results of research at the Nagari Children's Care Special School, Akabiluru District, family social support for children with special needs is emotional support, informative support, instrumental support, and assessment/award support.